OIKOS The two faces of organization [review of] - Hamoy, Hilda C. (Philippine Journal of Public Administration, 1992)
A review of Leonardo R. Silos, OIKOS: The Two Faces of Organization (Manila: Asian Institute of Management, 1991), ix + 250 pp.